Hubungan Pola Pemberian Makan Terhadap Angka Kejadian Stunting di Sleman Daerah Istimewa Yogyakarta - Chiesa Vidyananda Christi, Angela; Setiyorini, Ana; Wulandari, Riski (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2026)
Stunting is a condition of growth failure that occurs in toddlers due to chronic malnutrition. To date, stunting remains an unresolved nutritional problem. This condition can cause long-term problems, such as affecting the child's physical, mental, cognitive, and intellectual development. The purpose of this study is to identify the relationship between feeding patterns and the incidence of stunting in one village in Yogyakarta. The study used a cross-sectional method with a sample size of 127 toddlers and 127 parents of toddlers as respondents, selected using purposive sampling technique. Data collection was done using a questionnaire that had been tested for validity and reliability, as well as through measuring the height of toddlers. The data was then analyzed using the Chi-Square test with a significance level of <0.05. The research results show that 18 people (52.9%), or more than half of the parents, provided their children with the correct dietary patterns, and their children did not experience stunting. Meanwhile, 71 people (76.3%), the majority of parents who provided incorrect dietary patterns, had children who experienced stunting. Statistical analysis shows a significant relationship between feeding patterns and the incidence of stunting, with a p-value of 0.002. There is a relationship between feeding patterns and the incidence of stunting. It is hoped that future researchers can